2015
DOI: 10.1186/s13071-015-0754-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-insecticide susceptibility evaluation of dengue vectors Stegomyia albopicta and St. aegypti in Assam, India

Abstract: BackgroundDengue is rapidly expanding mosquito-borne viral infection globally facing operational challenges due to insecticide resistance in dengue vectors. We have studied the susceptibility status of potential dengue vectors St. albopicta and St. aegypti to the commonly used insecticides.MethodsStegomyia larval bioassays were carried out to determine LC10, LC50 and LC99 values and resistance ratios (RR50 and RR99) for temephos. Adult susceptibility bioassay to 4% DDT, 0.05% deltamethrin, 5% malathion was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
3
21
1
Order By: Relevance
“…As a consequence, there are plenty of resistance registers against PY in Aedes and Anopheles mosquitoes [26, 27], including some Ae. albopictus populations [20, 22, 28, 29]. …”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, there are plenty of resistance registers against PY in Aedes and Anopheles mosquitoes [26, 27], including some Ae. albopictus populations [20, 22, 28, 29]. …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the vector mosquitoes were under tremendous pressure from pyrethroid for a long period, which is reflected by the higher level of tolerance to it. Other vector mosquito species were found to be tolerant to pyrethroid, which were reported from other parts of the country (14)(15)(16)18,21).…”
Section: Discussionmentioning
confidence: 63%
“…Besides, synthetic pyrethroids have been widely used in LLINs, while DDT is used for IRS in many malaria-endemic regions including northern districts of West Bengal. Some recent studies have indicated a considerable level of resistance among different vectors against synthetic pyrethroids and DDT in different states of India (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Original Articlementioning
confidence: 99%
“…There are numerous reports documenting the establishment and increase of resistance to DDT in Ae. aegypti as a worldwide phenomenon, likely due to prolonged usage of DDT in vector control programs [14][15][16][17] during the latter half of the last century. These data were consistent with those previously reported for OX513A in relation to Malaysian Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Malathion is routinely used in fogging operations for mosquito control during the peak epidemic periods of Japanese encephalitis and dengue in northeastern states, due to which the dengue vectors in the environment are at continuous selection. It has been suggested that this poses a threat to efficacy of malathion in the long-term [17].…”
Section: Discussionmentioning
confidence: 99%